PEMBUATAN MOBILE GAME VIRTUAL PET ONLINE - Amelia Maya Christina; Richard Pramono; Marcellinus Ferdinand Suciadi (CALYPTRA, 2018)
Game virtual pet is a simulation game about the raising of an animal . This game can be played using mobile phone that has the Android operating system. In general, this game is more attractive to female players than male players, and sometimes given feature can make the player feel bored. Therefore made virtual pet online game that is not boring when played by female and male players, by providing additional gameplay and use the social media. Gameplay additions provided that battle, training, evolution, help friend, and transaction. For social media features, adding friends can be done automatically using Facebook. Making virtual pet online game using Unity3D application, by utilizing the programming language C# and PHP. To view and assets used in the manufacturing of virtual pet online game was created using Adobe Illustrator. After doing the implementa t ion and testing by interview showed that the application is made to increase the interest of female and men players to play for their gameplay additions and can be played without having to meet first.